An Innovative Policy for Rural Development ? Rethinking Barriers to Rural Communities Earning Their Living from Forests in Indonesia - Maryudi, Ahmad (Fakultas Kehutanan UGM, 2014)
The government of Indonesia (GoI) has trialed a number of community forestry schemes, ranging from collaborative management to long-term forest management rights handed to local communities, and implements them in state forestland. This policy shift toward community forestry in Indonesia shows an emerging signal on acknowledgement on the ability of local forest users to manage forest resources sustainably, and gives the people opportunities to benefit from the resources and eventually improve their daily life. With so much of promises community forestry brings, this paper primarily asks why the program is yet to meet the high expectation of rural development, tackling the pervasive rural poverty. It aims to identify, analyze and address key constraints of rural communities in exercising their rights which are considered as key factors to improve their livelihood and alleviate rural poverty. That the government-initiated community forestry schemes fall short of the initial targets in terms of the extent of state forestland areas managed by to forest communities to a large extent is explained by the regulatory barriers of tenurial uncertainties and the complex licensing procedures. Those coupled by the limited capacity as technical assistance rarely provided by government institutions appear to impede local people to secure better livelihood.